1999
DOI: 10.1038/sj.bjc.6690661
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 overexpression is an indicator of poor prognosis in resectable non-small cell lung cancer

Abstract: Cyclin D1 is one of the G1 cyclins that control cell cycle progression by allowing G1 to S transition. Overexpression of cyclin D1 has been postulated to play an important role in the development of human cancers. We have investigated the correlation between cyclin D1 overexpression and known clinicopathological factors and also its prognostic implication on resected non-small-cell lung cancer (NSCLC) patients. Formalin-fixed and paraffin-embedded tumour tissues resected from 69 NSCLC patients between stages I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…Different studies showed that three genes downstream from the pRb pathway that support cell growth, E2F, DP-1, and HDAC, are overexpressed in lung adenocarcinomas (Chang and Szabo, 2002;Gorgoulis et al, 2002;Singhal et al, 2003a). The expression of these Rb-dependent genes is increased probably because upregulation of cyclin D1 and cyclin D2, key regulators of pRb phosphorylation, and downregulation of cyclin-dependent kinase inhibitors p15, p21, p19, and p57 (Kawamata et al, 1995;Rusin et al, 1996;Gazzeri et al, 1998;Keum et al, 1999;Jin et al, 2001;Shoji et al, 2002;Singhal et al, 2003a). The TGFb/SMAD family pathway is an important regulator of several cyclin-dependent kinase inhibitors.…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%
“…Different studies showed that three genes downstream from the pRb pathway that support cell growth, E2F, DP-1, and HDAC, are overexpressed in lung adenocarcinomas (Chang and Szabo, 2002;Gorgoulis et al, 2002;Singhal et al, 2003a). The expression of these Rb-dependent genes is increased probably because upregulation of cyclin D1 and cyclin D2, key regulators of pRb phosphorylation, and downregulation of cyclin-dependent kinase inhibitors p15, p21, p19, and p57 (Kawamata et al, 1995;Rusin et al, 1996;Gazzeri et al, 1998;Keum et al, 1999;Jin et al, 2001;Shoji et al, 2002;Singhal et al, 2003a). The TGFb/SMAD family pathway is an important regulator of several cyclin-dependent kinase inhibitors.…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%
“…Not surprisingly, many human cancers (e.g. breast, parathyroid, head and neck, gastric, oesophageal) have increased cyclin D1 expression (reviewed in Hunter & Pines 1994), and cyclin D1 is a prognostic marker for many cancers (Bova et al 1999, Keum et al 1999, Samejima et al 1999, Cuny et al 2000, Itoi et al 2000. Moreover, forced overexpression of cyclin D1 results in a shortened G1 phase, reduced cellular dependence on exogenous mitogens, and cell transformation (Bodrug et al 1994, Wang et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…At the transcriptional level, kinase pathways such as p38/MAPK (mitogenactivated protein kinase), c-Jun N-terminal kinase/SAPK (stress-activated protein kinase), and p42/p44/ERK (extracellular signal-regulated kinase) transmit exogenous growth signals to up-regulate cyclin D1 (Lavoie et al 1996, Lee et al 1999. Similarly, activation of the Akt/ PKB (protein kinase B) pathway can increase cyclin D1 expression through either transcriptional (Gille & Downward 1999) or post-transcriptional mechanisms (Diehl et al 1998, Muise-Helmericks et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Notch-1 has been reported to increase the survival of NSCLC cells under hypoxic conditions by activating the insulin-like growth factor pathway (13). The expression of cyclin D1 (encoded by CCND1), a downstream target of Notch-1, is another indicator of poor prognosis for resectable NSCLC (14).…”
mentioning
confidence: 99%